2014
DOI: 10.1080/09583157.2014.903225
|View full text |Cite
|
Sign up to set email alerts
|

Effects of three mealybug species on the development, survivorship and reproduction of the predatory lady beetleCryptolaemus montrouzieriMulsant

Abstract: The lady beetle Cryptolaemus montrouzieri Mulsant (Coleoptera: Coccinellidae) is an important predator of mealybugs. The development, survivorship, longevity and reproduction of C. montrouzieri feeding on three different mealybug species [Dysmicoccus neobrevipes Beardsley, Ferrisia virgata Cockerell and Planococcus minor (Maskell)] were investigated in the laboratory at 26 ± 1°C, 75--90% RH and 14:10 (L:D) h photoperiod. Results indicated that, when feeding on different mealybugs, no significant differences we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…It has been the general observation in previous research studies that feeding of adult predators including coccinellids showed an increasing trend and reach peak, corresponding the mating and oviposition of females. Moreover, significant effect of prey densities has also been identified on the feeding of coccinellids as comparatively higher consumption is observed in lower prey densities than higher densities, mainly because of searching, handling and consumption of prey is comparatively easy at lower densities (Agarwala et al, 2001;Omkar and Srivastava, 2003;Rana, 2006;Qin et al, 2014;Saleem et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…It has been the general observation in previous research studies that feeding of adult predators including coccinellids showed an increasing trend and reach peak, corresponding the mating and oviposition of females. Moreover, significant effect of prey densities has also been identified on the feeding of coccinellids as comparatively higher consumption is observed in lower prey densities than higher densities, mainly because of searching, handling and consumption of prey is comparatively easy at lower densities (Agarwala et al, 2001;Omkar and Srivastava, 2003;Rana, 2006;Qin et al, 2014;Saleem et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…In China, C. montrouzieri is used as an effective natural enemy of mealybugs [3,26,27]. It has also been demonstrated that C. montrouzieri can complete its development (the development period of egg to adult is 29.3 ± 1.19 days) and reproduce (38.9 ± 4.43 eggs) when feeding on D. neobrevipes , and its finite rate of increase is 0.0546 [28].…”
Section: Discussionmentioning
confidence: 99%
“…It can feed on quite a broad range of mealybug species ( Kairo et al, 2013 ). And no significant change in developmental traits was observed in the use of different mealybug species ( Qin et al, 2014 ). However, it can also feed on aphids, whiteflies and the eggs of moths or other ladybirds under laboratory conditions ( Maes et al, 2014 ), suggesting potential non-target effects in its field use.…”
Section: Introductionmentioning
confidence: 97%